Disease-Causing Mutations and Rearrangements in Long Non-coding RNA Gene Loci - Aznaourova, Marina; Schmerer, Nils; Schmeck, Bernd; Schulte, Leon N. (Frontiers in Genetics, 2020)
The classic understanding of molecular disease-mechanisms is largely based on protein-centric models. During the past decade however, genetic studies have identified numerous disease-loci in the human genome that do not encode proteins. Such non-coding DNA variants increasingly gain attention in diagnostics and personalized medicine. Of particular interest are long non-coding RNA (lncRNA) genes, which generate transcripts longer than 200 nucleotides that are not translated into proteins. Amplifications, deletions and translocations affecting lncRNA loci were linked to severe human malignancies already years before the recent discovery of lncRNAs as an abundant class of cellular biomolecules. While most of the estimated 20,000 lncRNAs currently remain of unknown function, a growing number of genetic studies links lncRNA gene aberrations with the development of human diseases, including diabetes, AIDS, inflammatory bowel disease or cancer. This suggests that the protein-centric view of human diseases does not capture the full complexity of molecular patho-mechanisms, with important consequences for molecular diagnostics and therapy. This review illustrates well-documented lncRNA gene aberrations causatively linked to human diseases and discusses potential lessons for molecular disease models, diagnostics and therapy.